Assessing Effects of Inquiry-Based Learning in a Small Liberal Arts University General Education Mathematics Course - Melburg, Julie A. (Curtin University, 2024)
This research investigated effects of inquiry-based learning on students’ understanding of key concepts in a general education mathematics course. Data was collected over five semesters, including two online semesters. The research aimed to determine differences in student understanding of key concepts or attitude taught using inquiry-based learning, as compared to interactive lecture. The research findings address the differences found, both in the online and face-to-face mathematics classrooms. Implications of the research and implications are provided.